The Effect of Environmental, Social, and Governance (ESG) on Firm Performance With Earnings Management As a Moderation: Empirical Evidence Around COVID–19 - Redho Rahcmatulloh; Eddy Suranta (Yayasan Ilomata, 2023)
The primary goal of this research is to elucidate the influence of Environmental, Social, and Corporate Governance (ESG) performance on a company's overall performance. The research employs the ESG level as the independent variable for evaluation, which is the novelty of the study. The performance of the corporation is evaluated using various indicators, including financial performance (ROA), profitability (ROE), and Tobin's Q, which are regarded as reliant variables. Additionally, the study introduces the Modified by Jones Model of earnings management as a moderating factor. The analytical approach encompasses the application of multiple linear regression techniques. To ensure a representative sample, we conducted purposive sampling to select 120 observations from manufacturing companies listed on the Indonesian Stock Exchange that consistently maintained their ESG index during the period spanning from 2018 to 2022, including the turbulent period of the COVID-19 pandemic. The findings of this research reveal that the ESG index exerts a positive and statistically significant influence on ROA, ROE, and Tobin's Q. Furthermore, it is noteworthy that earnings management does not possess the capacity to moderate the relationship between ESG and company performance. The implications of this study are substantial, as it lends support to the application of legitimacy theory and agency theory in the context of ESG and corporate performance. However, it's important to acknowledge that the study's scope is limited to Indonesia, and consequently, the findings may not be directly applicable to other developing nations.